Peak hand-grip force predicts competitive performance in elite female cross-country skiers - Carlsson, M.; Carlsson, T.; Olsson, M.; Brorsson, S.; Malm, C.; Tonkonogi, M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
The relationship between grip force and racing success has previously been evaluated for non-elite male skiers and no significant correlation was found (Niinimaa et al., 1978). However, no study has investigated if there is an association between grip force and competitive performance for elite female cross-country skiers. Therefore, the purposes of the study were: 1) to investigate the relationship between mean peak hand grip force (GF) and competitive performance for elite-standard female cross-country skiers and 2) to examine if GF is related to mean lean mass in the arms (LM). Methods: Fifteen elite female cross-country skiers (age: 22.7 ± 3.0 years (mean ± SD), body mass: 60.2 ± 5.4 kg, stature: 169.5 ± 6.3 cm) completed a grip force test (Grip-it, Brorsson Innovation AB, Falun, Sweden) to determine peak force for both hands and a dual-energy x-ray body composition test (GE Healthcare Lunar, Madison, USA) to determine LM. Performance data were collected from a sprint prologue race in classical technique (SPR) and a 10-km distance race in free-style technique (DR). Statistical analyses were processed using SPSS with all tests performed at an alpha of 0.05. Results: The test variables obtained were GF: 307.3 ± 53.0 N and LM: 2.5 ± 0.3 kg. Mean completion time for SPR and DR were 262.5 ± 12.3 s (n = 12) and 1828.7 ± 84.7 s (n = 10), respectively. The GF were correlated with SPR (r = -0.69, P = 0.012), DR (r = -0.73, P = 0.016), and LM (r = 0.78,